PENGARUH NILAI SAHAM, FINANCIAL LEVERAGE, DAN PAJAK PENGHASILAN TERHADAP PERATAAN LABA (STUDI KASUS PERUSAHAAN BATUBARA DAN MIGAS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Poppy Mardiana; Nina Yulianasari (Universitas Prof.Hazairin,SH Bengkulu, 2018)
This study aims to determine how much influence the value of shares, financialleverage, income tax on income smoothing. The population of this study is all coal andoil and gas companies listed on the Indonesia Stock Exchange in 2012-2016. Thesampling technique used purposive sampling which amounted to 20 samples. The datasource is secondary data. Data published on the Indonesia Stock Exchange. Themethod of analysis uses Multiple Linear Regression and data testing is done with thehelp of program eviews (econometric views).The results of this study indicate that stock values and financial leverage have no effecton income smoothing while income tax has an effect on income smoothing